An Approach of a Research Tool based in a Shamanic Interface - Tiago Susano Pinto (2015)
Nowadays gesture recognition systems are developed for several purposes, e.g. entertainment, security or education. Such interfaces are controlled by gestures performed by a user, and these gestures are not only associated with a command in the system but also have an intrinsic meaning to the user. Since gestures can have different meanings for users based on their cultural background, this thesis adopted the perspective of using a shamanic interface. A shamanic interface considers a person's cultural background for gesture-based interaction. From a software architecture perspective, shamanic interfaces use a cultural layer that considers a user's culture when linking a gesture to a certain command. This supports different user experiences with the same interface using gestures linked to a user's culture. Being a recent proposal, the shamanic interface lacks empirical testing and validation, hence this thesis' contribution is the creation of a research tool to enable empirical research of the concept. After developing a cultural layer, a game was implemented and evaluated to test its performance and applicability. For recognising gestures, the cultural layer relies on a Leap Motion Controller. A Leap Motion Controller can track gestures with a certain precision without requiring the user to wear cumbersome tracking devices. For recognising and classifying gestures, Hidden Markov Models and a respective classifier were used. By developing a game with a shamanic interface and performing usability tests with users with different cultural backgrounds, it can be concluded that this research tool can be used by empirical researchers to test and develop the concept. Shamanic interfaces are promising, but further work needs to be done on the gesture recognition area as well as in the definition of meaningful cultural gestures.